HOW EXCLUSIVE IS “EXCLUSIVE”? AN EXAMINATION OF SECTION 18 OF THE FEDERAL COURT ACT - Kaufman, Donna (Revue de droit de l'Université de Sherbrooke, 1985)
Section 18 of the Federal Court Act provides that the Trial Division of the Federal Court has "exclusive original jurisdiction" to issue certain prerogative writs or grant declaratory relief "against any federal board, commission or other tribunal". In the early days of the Court, it was thought (in the words of W.R. Jackett, its first Chief Justice), that provincial superior courts were now without jurisdiction to exercise their traditional superintending and reforming powers over these federal boards, commissions or other tribunals. But this was soon challenged, and in a trilogy of cases, decided in 1982 and 1983, the Supreme Court of Canada clarified the meaning of "exclusive", as used in section 18 of the Act. This article traces the legislative history of the section, and it analyzes what was held in the three leading cases. The picture which emerges is that the Federal Court's jurisdiction is neither as exclusive as the word would suggest nor as its draftsmen had envisaged.